Kaitan Luas Permukaan Pot Bonang Dengan Frekuensi Nada Dasar Yang Dibangkitkan - Pebriani, Putri Hesti; Munir, Rahmawati; Natalisanto, Adrianus Inu (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2023)
One of the musical instruments in the gamelan is the bonang instrument. A bonang is a musical instrument with a small, hollow structure. This study was conducted to determine the relationship between the surface area of the bonang pot and the frequency of the basic tone generated, and to find out the results of the variety of sounds on the bonang musical instrument. A bong that was stopped only after the sound was muted was applied to record the audio directly. Using AudioCyti software, a surface area and frequency are then measured, and the output signal is measured using the Fourier transform method. The parameters measured are surface area and frequency. In accordance with the results of this study, there is a connection between surface area, or the basic frequency, which is achieved with a frequency of 0.88363, and frequency, which is obtained with a frequency of 0.986053. So, it is concluded from the study that has been carried out that the surface area has an influence on the frequency. Users can determine the frequency of a bonang musical instrument's fundamental tone by varying its frequency values from lowest to highest and analyzing the output signal with audiocyti software. As a result, each sound produced by a bonang pot is distinct and nonsequential. This is because, like modern musical instruments, a bonang laras slendro does not yet have a set tone frequency.